2009
DOI: 10.1364/ol.34.001642
|View full text |Cite
|
Sign up to set email alerts
|

Time-multiplexed dual-focal plane head-mounted display with a liquid lens

Abstract: Focus cues play a significant role in three-dimensional (3-D) depth perception. Conventional stereoscopic displays, however, lack the ability to correctly render these cues, because they present a pair of stereoscopic images on a fixed image plane while forcing the eyes to converge at different distances to view objects at different depths. Using a fast liquid-lens device, we present the design and implementation of a time-multiplexed dual-focal plane display that is capable of rendering correct or near-correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 9 publications
0
55
0
Order By: Relevance
“…Goldring et al [2006] has adapted a display with lenses to focus the image on the center of the eye lens improving readability. In the same way, Liu and Hua [2009], and Rolland et al [2000] have introduced dynamic lenses that change the plane of focus and a stack of planes that are selectively illuminated to create volumetric head-mounted displays. These techniques, however, require moving parts and do not account for non-symmetric aberrations, such as astigmatism, higher-order aberrations, and cataracts.…”
Section: Related Workmentioning
confidence: 99%
“…Goldring et al [2006] has adapted a display with lenses to focus the image on the center of the eye lens improving readability. In the same way, Liu and Hua [2009], and Rolland et al [2000] have introduced dynamic lenses that change the plane of focus and a stack of planes that are selectively illuminated to create volumetric head-mounted displays. These techniques, however, require moving parts and do not account for non-symmetric aberrations, such as astigmatism, higher-order aberrations, and cataracts.…”
Section: Related Workmentioning
confidence: 99%
“…These could be used for our purposes to some extent. Liu and Hua [2009] have shown a liquid lens based solution to change the plane of focus inside a head mounted display (HMD). Rolland et al [2000] showed a multiplanar volumetric display based on a stack of laminated planes that are selectively illuminated inside a HMD.…”
Section: Related Workmentioning
confidence: 99%
“…Things are getting worse when it is applied in augment reality or stereoscopic display, which limits the further development of HMDs. Many approaches have been proposed to solve this problem by generating dual or multiple focal planes in HMD, such as spatial-multiplexed [10] [11] and time-multiplexed methods [12] [13]. However, the complexity of these systems will be increased by employing multiple micro-displays or half mirrors in the spatial-multiplexed methods or by the active elements in the time-multiplexed methods.…”
Section: Introductionmentioning
confidence: 99%